ANALISIS TINGKAT METAKOGNISI SISWA DALAM PEMECAHAN MASALAH MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL - S.C.R Wicaksono; Mardiyana .; Siswanto . (UJMES (Uninus Journal of Mathematics Education and Science), 2021)
Metacognition is a person's awareness of using his thoughts to plan, consider, control, and assess the cognitive processes and strategies they have. To solve a mathematical problem requires awareness of the knowledge possessed and the awareness to do something that is thought and why it is done. This level of metacognition consists of Tacit Use, Aware Use, Strategic Use and Reflective Use. This study aims to describe the level of students' metacognition in solving problems with a two-variable linear equation system in class VIII MTs N 1 Lampung Timur Lampung. This research is a case study qualitative research. The subjects of this study were 3 students of class VIII MTs Negeri 1 Lampung Timur in the academic year 2020/2021. The subject selection procedure used purposive sampling technique. Data was collected by using test and interview methods. Validation of data using time triangulation. The results showed that the level of students' metacognition in solving problems of story problems in a linear equation system of two variables at the level of reflective use, aware use and tacit use.